(untitled) (World Economics and Finance Bulletin, 2022)
The article describes the sovereign credit rating and its specific features. Also, assessment of ratings by three credit rating agencies namely, Moody’s, Fitch Ratings and Standard & Poor’s is given to determine the position of country. Moreover, the most urgent issues of state finance, such as strengthening Uzbekistan’s position in the sovereign credit rating, thereby increasing the international image of our country, attracting foreign investments to the country, and financing the budget deficit from foreign sources, were studied.